Differential effects of endurance and resistance training on central fatigue - Triscott, S.; Gordon, J.; Kuppuswamy, A.; King, N.; Davey, N.; Ellaway, P. (Journal of Sports Sciences, 2008)
The effect of long-term endurance and resistance training on central fatigue has been studied using transcranial magnetic stimulation by exercising the biceps brachii to exhaustion and recording motor-evoked potentials from the non-exercised homologous biceps. Three groups of eight healthy individuals took part: two groups of individuals who had more than 8 years of athletic training in either an endurance or resistance sport, and a group of controls. The size of a motor-evoked potential (area of averaged rectified response) was significantly depressed in all three groups in the non-exercised arm after exhaustive exercise of the opposite arm. Recovery of motor-evoked potentials occurred earlier in endurance athletes (20 min) than in control participants (30 min) and resistance athletes (>30 min). Dexterity and maximum voluntary contraction of the biceps for the non-exercised arm were not depressed in any group. In a separate session, the limit of endurance time for the biceps was reduced significantly following exhaustive exercise of the biceps of the other arm for resistance athletes and control participants, whereas there was no change in the endurance athletes. Our findings suggest that athletic training has an effect on the mechanism of central fatigue that may be specific to the nature of training.